Light adaptation strategies of Quercus mongolica at different ages in four plantations - Guoru Tang; Hao Zhang; Honglin Xing; Tianhe Yuan; Andrey A. Gontcharov; Ling Yang (Forestry Research)
This study investigated the allocation strategies of non-structural carbohydrates and functional traits in Quercus mongolica seedlings of different ages under different light conditions. The study took place at the Urban Forestry Demonstration Base in Harbin City, Heilongjiang Province, China. Seedlings of three age classes were collected in two light environments, the forest edge and the forest understory. By measuring specific leaf area, biomass, soluble sugar concentration and starch concentration, we revealed the growth adaptation strategies and responses to different light conditions in Q. mongolica seedlings of different age classes. Our results show that the adaptation strategies of seedlings of different age classes are very different. First, our study showed a strong coordination of soluble sugars between roots, stems, and leaves of 1−2 year old Q. mongolica seedlings, indicating an efficient partitioning of carbon between organs at this age. In 3−4 year old Q. mongolica seedlings, a significant negative correlation was observed between starch in the roots and soluble sugars in the leaves, indicating the transformation of various non-structural carbohydrates. In addition, 5−6 year old seedlings start to increase their investment in the above-ground part to achieve a height advantage. In conclusion, this study improves our understanding of the light adaptation strategies of Q. mongolica seedlings and provides valuable insights for the natural regeneration and management of Q. mongolica forest vegetation.